2021
DOI: 10.3390/ma14185413
|View full text |Cite
|
Sign up to set email alerts
|

Durability of a New Thermal Aerogel-Based Rendering System under Distinct Accelerated Aging Conditions

Abstract: The widespread application of innovative thermal enhanced façade solutions requires an adequate durability evaluation. The present work intends to assess the durability of a new aerogel cement-based rendering system through the adaptation of different accelerated aging cycles, such as heating–freezing, freeze–thawing, and heat–cold. Several mechanical properties and also capillary and liquid water absorptions were tested for uncoated and coated specimens. A decrease in the mechanical strength, especially after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 52 publications
(61 reference statements)
0
15
0
1
Order By: Relevance
“…A study by Ibrahim et al revealed that the application of an additional insulation layer in the form of a silica aerogel-based render on an uninsulated building or on a building with existing interior insulation results in a reduction in or complete removal of the moisture problem [ 111 ]. Moreover, Maia et al demonstrated that the application of an additional protective layer to aerogel reduces the negative effects of accelerated aging and results in increased durability of the mortars over a longer service life [ 113 ].…”
Section: Durability and Performance Of Silica Aerogel-based Cementiti...mentioning
confidence: 99%
“…A study by Ibrahim et al revealed that the application of an additional insulation layer in the form of a silica aerogel-based render on an uninsulated building or on a building with existing interior insulation results in a reduction in or complete removal of the moisture problem [ 111 ]. Moreover, Maia et al demonstrated that the application of an additional protective layer to aerogel reduces the negative effects of accelerated aging and results in increased durability of the mortars over a longer service life [ 113 ].…”
Section: Durability and Performance Of Silica Aerogel-based Cementiti...mentioning
confidence: 99%
“…Building components differential movements and the lack of capacity of the render to follow the deformation of the substrate, could lead to tensions and cracking. The combined action of temperature and water highly contribute to the degradation of renders [33]. The freeze-thawing of water retained in the pores could lead to cracking.…”
Section: Climate-induced Degradation Of Rendered Façades: Degradation...mentioning
confidence: 99%
“…Furthermore, the declared material properties of these ACMs are, like for other building materials, based on laboratory measurements and analyzed under controlled climatic conditions. Likewise, and apart from a number of studies in the laboratory [ 5 , 6 , 7 ], the correlation between the declared moisture properties of ACMs and their long-term performance when exposed to real climate loads in the field is not yet confirmed. This could partly be because the material is relatively new but also due to the fact that moisture safe design is practiced mainly in regions with high moisture loads on buildings [ 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 97%
“…The range of measured A cap was 0.48–2.8 kg/m 2 ·min 0.5 , which is higher than the stated requirement (less than 0.4 kg/m 2 ·min 0.5 ) in EN ISO 998-1. Furthermore, in [ 5 , 6 , 7 , 24 , 25 , 26 ], the long-term performance of trial mixtures of ACMs was studied using artificial weathering cycles in the laboratory. Trial mixtures of ACMs were produced in the laboratory by mixing aerogel granules to a mortar mixture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation